(3TQM UMjM eSdes - (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s ((3EHQGgje Hf CMeO Hf eMeO GdOQYj s)
(3ChdgG (B:s
(3cJGH GdWGYhf hGdWjQI hGdcgGfI hfMhgG bhdg Udi Gddg Ydjg hSde aj GdWGYhf Gfg QLRkG CQSd Ydi Hfj ESQGFjd hYdi ef cGf bHdce aEPG SeYJe Hg HCQV dG JbOehGYdjg hEPG hbY HCQV hCfJe HgG adG JNQLhG aQkG efg s
(3BNQgG (B:s
(3hbO YedJ GdUMGHI aef QaYg hPcQ daXg hdGjMUd HgPG EVWQGH hGddg CYde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
(3cTa GdXfhf (B- (3GdLRA (B1 - (3U (B555 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B557s
Keywords: (3GdMOjK h GdeUWdMs